Historical and Ethical-Ideological Conditionality of Literary Interpretations of Gavrilo Princip - Melida Travančić (Pannoniana, 2017)
Sarajevo assassination and its assassin Gavrilo Princip have been a subject to many artistic achievements, starting from literary, artistic, theatrical to music works, almost a hundred years. The paper deals with the historical impact of the topic on the literature, that is how the assassination and its participants led by Gavrilo Princip were interpreted in the literature, and the way the historical and literary discourse is interwoven in the very interpretation. In the paper, an emphasis is on the different perception of Sarajevo assassination and its assassin Gavrilo Princip within Bosnian and Herzegovinian, Croatian and Serbian literature and the impact it has on the literature in different social and historical contexts. On one hand, these are the writers who used the literature as a medium for the projection and affirmation of the historical truth, upon which they agree, and on the other hand, there are literary works which used the historical event as an inspiration and still maintained the aesthetical – ethical dignity, not becoming a servant to any ideology.